Mesoporous Tin‐Based Oxide Nanospheres/Reduced Graphene Composites as Advanced Anodes for Lithium‐Ion Half/Full Cells and Sodium‐Ion Batteries. Issue 55 (4th September 2017) - He, Yanyan; Li, Aihua; Dong, Caifu; Li, Chuanchuan; Xu, Liqiang
Abstract: The large volume variations of tin‐based oxides hinder their extensive application in the field of lithium‐ion batteries (LIBs). In this study, structure design, hybrid fabrication, and carbon‐coating approaches have been simultaneously adopted to address these shortcomings. To this end, uniform mesoporous NiO/SnO2 @rGO, Ni‐Sn oxide@rGO, and SnO2 @rGO nanosphere composites have been selectively fabricated. Among them, the obtained NiO/SnO2 @rGO composite exhibited a high capacity of 800 mAh g −1 at 1000 mA g −1 after 400 cycles. The electrochemical mechanism of NiO/SnO2 as an anode for LIBs has been preliminarily investigated by ex situ XRD pattern analysis. Furthermore, an NiO/SnO2 @rGO‐LiCoO2 lithium‐ion full cell showed a high capacity of 467.8 mAh g −1 at 500 mA g −1 after 100 cycles. Notably, the NiO/SnO2 @rGO composite also showed good performance when investigated as an anode for sodium‐ion batteries (SIBs). It is believed that the unique mesoporous nanospherical framework, synergistic effects between the various components, and uniform rGO wrapping of NiO/SnO2 shorten the Li + ion diffusion pathways, maintain sufficient contact between the active material and the electrolyte, mitigate volume changes, and finally improve the electrical conductivity of the electrode. Abstract : High performance : A series of tin‐based oxides@rGO composites with microporous or mesoporous nanospherical structures has been fabricated from the same precursor of NiSn(OH)6 nanospheres by a facile hydrothermal method (see figure). The resultant materials demonstrated enhanced electrochemical performances when applied as anodes for lithium‐ion and sodium‐ion half cells, and lithium‐ion full cells.